2013
DOI: 10.1098/rspa.2012.0696
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory study of wave crest statistics and the role of directional spreading

Abstract: This paper concerns the crest height statistics arising in sea states that are broad banded in both frequency and direction. A new set of laboratory observations are presented and the results compared with the commonly applied statistical distributions. Taken as a whole, the data confirm that the crest-height distributions are critically dependent upon the directionality of the sea state. Although nonlinear effects arising at third order and above are most pronounced in uni-directional seas, the present data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 51 publications
9
53
0
Order By: Relevance
“…If the water surface is steep, but not sufficiently steep, the impact will be replaced by very large run-up velocities. Although recent research [28] has shown that large incident sea states will be steeper than is commonly predicted, with a higher than expected occurrence of wave breaking, this alone is not sufficient to explain the occurrence of wave impacts on the columns of some offshore structures. Indeed, both field observation and extensive model testing have shown that columns that are large, but not so large that they lie in the linear diffractions regime, are particularly susceptible to both wave impacts and large run-up velocities.…”
Section: Wave Steepness Wave-wave Interactions and Practical Implicamentioning
confidence: 92%
“…If the water surface is steep, but not sufficiently steep, the impact will be replaced by very large run-up velocities. Although recent research [28] has shown that large incident sea states will be steeper than is commonly predicted, with a higher than expected occurrence of wave breaking, this alone is not sufficient to explain the occurrence of wave impacts on the columns of some offshore structures. Indeed, both field observation and extensive model testing have shown that columns that are large, but not so large that they lie in the linear diffractions regime, are particularly susceptible to both wave impacts and large run-up velocities.…”
Section: Wave Steepness Wave-wave Interactions and Practical Implicamentioning
confidence: 92%
“…In this study, the appropriate weighting is based upon a normal distribution with a standard deviation of σ θ in accordance with the directional distribution outlined in equation (2.8). This method was previously adopted in [26,27] and formed the basis of the earlier laboratory study outlined in [6]. Given that this study is specifically concerned with the directionality of the sea state, the merits of these approaches need to be carefully considered.…”
Section: Directional Wave Generationmentioning
confidence: 99%
“…Indeed, this study concerns a subset of four of these sea states, the details of which are given in table 2. The original data, full details of which are given in [6], concern time-histories of the water surface elevation, η ( t ), recorded over the working area of the wave basin. This study uses η ( t ) data recorded at one representative position, located 4.75 m downstream of the wave paddles.…”
Section: Experimental Procedures and Test Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…Beforehand, it can be argued that the effect of the Benjamin-Feir instability may be very mild, because the value of k D = 1.6 of the sea is just above the critical value 1.36, and the spreading is wide which could reduce the steepness as observed in extensive laboratory experiments of Latheef and Swan (2013). The steepness, which, for unidirectional waves, would give k Hs/2 = 0.14, turns out to be much larger, up to a factor 5, in the simulations near high crests.…”
Section: Introductionmentioning
confidence: 99%